The Pattern Evoked Electroretinogram: Origin, Characteristics and Clinical Usage - Lovasik, J.V.; Kothe, A.C. (Canadian Journal of Optometry, 2021)
This paper consists of a literature review of the clinical observations of the pattern electroretinogram (pERG) and theories concerning its origin. Normative data are presented for subjects aged 20 to 29 years to document variations in pERG response characteristics as a function of selected stimulus parameters. Clinical cases of visual neural dysfunction are also presented to illustrate the usage of pERGs in the realm of electrodiagnostic testing. Emphasis is placed on new or complimentary information provided by these retinal potentials.